PERANAN DANA ALOKASI UMUM DALAM PELAKSANAAN OTONOMI DAERAH (Jurnal Mahasiswa Pasca Sarjana, 2015)
This research was to examine the degree of fiscal independence Government  KabupatenKota in Central Java province. The data used in this research is secondary data composed of data DKF. DAK and DAK. As for the analytical techniques used multiple linear regression is a method. Based on the results of the analysis using the method of multiple linear regression indicated that DAK variables  influential are significant and have a negative relationship toward fiscal self-sufficiency in Government counties/cities  in the province of Central Java. This negative direction indicates that the increased allocation of Funds Specifically does not increase the fiscal independence in the region. Meanwhile, DAU variable does not affect the independence of the Government's fiscal counties/cities in Central Java province. It shows that an increase in the DAU does not increase the fiscal independence in the region. Thus it can be stated that the independence of the Government's fiscal counties/cities in Central Java province in the autonomous region are still low, or it can be stated that the level of dependency of the Government Center is still quite high. It is characterized from a proportion of the DAU Spending towards areas that are relatively more.Keywords: DAK, DAU and DKF